On the issue of diaspora's terminological dispersal. (1st June 2020) - Ogunyemi, Ola
This analytical scoping review contributes to the debate about the diaspora's terminological dispersal that has dominated scholarly discourse in the past two decades. The author argues that diaspora as a 'metaphoric designation' is a useful conceptual entry point to chart the multiplicity of ways in which diaspora research has evolved in the twenty-first century. From this premise, diaspora as a 'metaphoric designation' mitigates against the 'nostalgia-premised' definitions of diasporas and could resolve the concerns about 'terminological dispersal' that have proliferated in diaspora studies.